Evidence of Phosphonium‐Carbenium Dication Formation in a Superacid: Precursor to Fluorinated Phosphine Oxides. Issue 5 (28th December 2018) - Castelli, Ugo; Lohier, Jean‐François; Drukenmüller, Ines; Mingot, Agnès; Bachman, Christian; Alayrac, Carole; Marrot, Jérôme; Stierstorfer, Karin; Kornath, Andreas; Gaumont, Annie‐Claude; Thibaudeau, Sébastien
Abstract: Unambiguously confirmed by low‐temperature in situ NMR experiments, X‐ray diffraction and vibrational spectroscopy, phosphonium‐carbenium superelectrophiles are shown to be generated in strong acidic conditions. Representing crucial intermediates, their exploitation allows for the synthesis of unprecedented fluorinated (cyclic) phosphine oxides. Abstract : Superelectrophile : Phosphonium carbenium dications are formed by the protonation of unsaturated phosphine oxides in superacid. The superelectrophilic character of these dications is essential for the syntheses of various novel fluorinated and cyclic phosphine oxides.